Peran Agama dalam Kehidupan Bermasyarakat di Tatar Sunda Ciamis - Kemal Al Kautsar Mabruri; Diana Farid; Sofyan Mei Utama; Abdulah Pakarti, Muhammad Husni; Iffah Fathiah; Hendriana (Bayani, 2023)
Ciamis is one of the districts in Indonesia where the majority of the population adheres to Islam, but this does not stop them from socializing and mobilizing well with non-Muslim community members. Both live side by side with the values that they both uphold as religious people. This study aims to analyze the role of religion in social life in the Tatar Sunda Ciamis environment. This research uses a qualitative method that focuses on literature studies, both primary and secondary data. The results of this study show that with religion they realize that harmony and good communication are one of the important things that cannot be separated in realizing a safe, peaceful, civil and peaceful life.